Control estadístico de calidad en pasteurización del jugo “LIBER” Mix: Brix, pH y acidez cítrica - 2012 - Avalos Carranza, Carmen Patricia (2012)
This research was conducted in the company “Enrique Cassinelli e hijos” the goal was to determine if low Statistical Quality Control of juice pasteurization process "LIBER" Mix respect to Brix, pH and citric acidity during the period of January to March 2012._x000D_ Statistical analysis for the sensory quality univariate showed a normal distribution but also a normally distributed random vector showed Trivariante also be correlated together by the significance test Multivariate correlation (Bartlett sphericity test) that justified the application of the Hotelling's T2 test. The results showed that the pasteurization process is out of statistical quality control in the production line of Juice "LIBER" Mix as trivariate control chart_x000D_ It was therefore proposed an Improvement Plan for the area of Quality Assurance in the company to improve the production process in the line of nectars, avoid rework generated input costs and payment to the hand of the work as well as loss of time and resulting in low productivity